(untitled) (Zoological Records and Reviews, 2022)
Integrative taxonomy – the synthesis of multiple independent character systems for species delimitation and description – has emerged as the dominant paradigm in contemporary zoological systematics, superseding both classical morphological taxonomy and the brief but influential period of molecular-only species delimitation. This review traces the conceptual development of integrative taxonomy from its theoretical foundations in the works of Dayrat (2005) and Padial et al. (2010) to its current practice across major animal phyla, evaluating recent methodological advances and their impacts on species discovery and conservation. We review the application of integrative approaches across seven zoological domains – vertebrate systematics, invertebrate taxonomy, parasitology, marine biology, entomology, herpetology, and freshwater biology – based on analysis of 312 systematic studies published between 2015 and 2021. Key methodological advances include the integration of geometric morphometrics, bioacoustics, environmental DNA, population genomics (RADseq, whole-genome sequencing), and ecological niche modelling into standard taxonomic workflows. Integrative approaches have increased the rate of new species descriptions by an estimated 34.8% over morphological-only approaches while simultaneously reducing the rate of taxonomic inflation (over-splitting) by 28.4%. We identify the primary remaining barriers to universal adoption of integrative taxonomy – cost, expertise, access to facilities – and propose practical solutions including community-based infrastructure, open-access databases, and standardised reporting frameworks. Conservation applications of integrative taxonomy, including range delineation, management unit identification, and IUCN assessment support, are evaluated and prioritised.